Resolving the 150-year-old homonymy of Laranda: A new name for the cricket genus (Orthoptera: Phalangopsidae: Paragryllinae) - Campos, Lucas Denadai De; Souza-Dias, Pedro G. B. (Zootaxa, 2025)
The genus name Laranda presents a significant case of zoological homonymy, requiring nomenclatural action under the International Code of Zoological Nomenclature (ICZN). Laranda Kinberg, 1865 (Polychaeta), established for marine annelids, predicts Laranda Walker, 1869 (Orthoptera), a distinctive genus of Neotropical crickets. This homonymy, unnoticed for over 150 years, was recently identified in the Taxonomic Catalog of the Brazilian Fauna. To ensure nomenclatural stability and universality, we propose Unacla nom. n. as a replacement name for the cricket genus Laranda Walker, 1869, which is a junior homonym and, therefore, invalid. This note details the type material and distinguishing features of both taxa, justifying the proposed name change and its implications for systematics.